Corporate Social Responsibility (CSR), Firm Size, Profitability, and Leverage on Earnings Response Coefficient (ERC) - Noer Sasongko; Ragil Kuning Puspawati; Kusuma Wijayanto (Universitas Muhammadiyah Surakarta, 2020)
This study aims to examine the effect of corporate social responsibility (CSR), company size, profitability and leverage on earnings response coefficient (ERC). This type of research is quantitative. The type of data used is secondary data obtained from www.idx.co.id.The population used in this study is manufacturing companies that was listed on the Indonesia Stock Exchange during the 2015-2018 period. While this research sample was determined by purposive sampling method in accordance with predetermined criteria. The analytical method used is multiple linear regression analysis.The results of this study indicate that what has an effect on earnings response coefficient is corporate social responsibility and company size. While profitability and leverage have no effect on earnings response coefficient. Keywords: corporate social responsibility, company size profitability, leverage, earnings response coefficient